21ST CENTURY TEACHING AND LEARNING: IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEM (LMS) IN EDUCATION - Pavita Kusuma Ningayu Saputri (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
The world-facing rapid growth in technology, particularly in education. In the implementation of the learning management system (LMS) in 21st century, society have proceeded against high intellectual behaviors with cybernated knowledge-based. Modern society requires the education practitioners and the learners to enhance their information communication technology within an e-learning situation where distant learning exist. A learning management system is a medium of teaching-learning for both educators and learners. It provides a bunch of avant-garde technology that support the learning process. There are advantages also disadvantages while using LMS as the core in modern language learning education. Keywords: 21st-century education and skill, e-learning, ICT, LMS.